(untitled) (Canadian Eye Care Today, 2023)
Glaucoma is a progressive optic neuropathy which is relatively uncommon in childbearing age, with a reported prevalence of 0.16% between the ages of 18-40 years. Glaucoma management among pregnant patients presents a challenging scenario to the treating physician. Even with its low prevalence in the United Kingdom, a country-wide survey has revealed that approximately 26% of ophthalmologists reported having treated a pregnant patient with glaucoma. Perhaps due to this low prevalence, 31% of these ophthalmologists reported uncertainty about managing glaucoma in this population. When treating pregnant or breastfeeding patients, one must consider the benefit of treatment for the mother while weighing this against the risks the treatment may pose for the mother and fetus/child. This highlights the importance of having a review which can serve as a reference for physicians when managing glaucoma in pregnant and/or breastfeeding patients.